Induction and repair of X-ray damage in mammalian cell cultures treated with membrane-active drugs. - Bertsche, U. (Nature Publishing Group, 1984)
Cultures of Ehrlich ascites tumour cells (EATC) were treated before and after X-irradiation with the membrane active drugs chlorpromazine (CPZ) and procaine. Under hypoxic conditions of irradiation CPZ sensitized cells and was most effective at about 50 microM, whereas at higher drug concentrations the extent of sensitization was less. Sensitization was however not observed in cultures supplemented with vitamin E. Likewise, CPZ inhibited repair of potentially lethal damage (RPLD) measured by delayed plating of stationary cell cultures either using the colony forming ability or micronucleus formation as endpoints. Procaine, on the other hand, was found to sensitize cells only slightly under hypoxia and protected slightly under oxic conditions in the concentration range from 10-100 mM. Both drugs induced an increase in ATP content at these concentrations. Since it has also been observed that these drugs cause depletion of intracellular sulfhydryl groups which may serve for protection of membrane sites, it is assumed that the radiobiological effects observed arise mainly from an influence on cellular and nuclear membranes where lipid bilayer fluidity and conformational status of membrane-bound enzymes may be changed. The possible role of heterochromatin anchored or near to the nuclear membrane as a radiation sensitive compartment of the cell is discussed.